2018
DOI: 10.1186/s13568-018-0538-y
|View full text |Cite
|
Sign up to set email alerts
|

New keratinolytic bacteria in valorization of chicken feather waste

Abstract: There is an increasing demand for cost-effective and ecologically-friendly methods for valorization of poultry feather waste, in which keratinolytic bacteria present a great potential. Feather-degrading bacteria were isolated from living poultry and a single strain, identified as Kocuria rhizophila p3-3, exhibited significant keratinolytic properties. The bacterial strain effectively degraded up to 52% of chicken feathers during 4 days of culture at 25 °C. Zymographic analysis revealed the presence of two domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…As a result of microbial growth and metabolism of amino acids derived from protein hydrolysis, increases in turbidity and pH of the medium were observed, demonstrating the ability of this bacterium to efficiently degrade keratin [30]. The keratin degradation ability of C. diversus demonstrated in this study (~85% in 36 h) was higher than that of the bacterium Kocuria rhizophila strain p3-3, which was previously reported to degrade only 52% of chicken feathers in 96 h of fermentation in submerged culture [31]. In contrast, the keratin degradation ability of C. diversus was similar to that of the Alcaligenes sp.…”
Section: Discussionmentioning
confidence: 47%
“…As a result of microbial growth and metabolism of amino acids derived from protein hydrolysis, increases in turbidity and pH of the medium were observed, demonstrating the ability of this bacterium to efficiently degrade keratin [30]. The keratin degradation ability of C. diversus demonstrated in this study (~85% in 36 h) was higher than that of the bacterium Kocuria rhizophila strain p3-3, which was previously reported to degrade only 52% of chicken feathers in 96 h of fermentation in submerged culture [31]. In contrast, the keratin degradation ability of C. diversus was similar to that of the Alcaligenes sp.…”
Section: Discussionmentioning
confidence: 47%
“…Reducing power and radical scavenging were also displayed by feather hydrolysates produced by Bacillus sp. MPTK6 [37], and Kocuria rhizophila p3-3 [38]. Such potentials were also verified for hydrolysates of delimed tannery fleshings obtained by 4-day cultivations with Enterococcus faecium NCIM5335 [39], for shrimp shell waste hydrolysates produced by P. aeruginosa A2 [40].…”
Section: Resultsmentioning
confidence: 82%
“…[25]. Laba et al [26] and Mamangey et al [27] reported keratinase production by Kocuria rhizophila and Azotobacter chroococcum at 180 rpm. Optimal keratinase production by Actinomadura keratinilytica [28], Bacillus amyloliquefaciens [29] and Chryseobacterium sediminis [30] has been reported at 200 rpm, while optimal keratinase production from Bacillus licheniformis has been reported at 250 rpm [31].…”
Section: Discussionmentioning
confidence: 99%